Significant enhancement of anti-friction capability of cationic surfactant by phosphonate functionality as additive in water. (August 2017) - Wang, Yurong; Yu, Qiangliang; Ma, Zhengfeng; Huang, Guowei; Cai, Meirong; Zhou, Feng; Liu, Weimin
Abstract: A new N-(3-(diethoxyphosphoryl)propyl)-N, N-dimethyloctadecan- 1-ammonium bromide (NP) surfactant was synthesized. The NP together with 1 wt% sodiumD -gluconate or 1 wt% triethanolamine displays remarkable lubricating property as the water-based lubricant additive and provides a non-corrosive environment for steel in aqueous solution. The lubricating mechanism was tentatively discussed according to electrical contact resistance, X-ray photoelectron spectroscopy and Quartz Crystal Microbalance measurement. These results show a stable protective film is formed on the contact surface by physical adsorption and tribo-chemical reactions. Surprisingly, the water-based additive has excellent anti-friction properties comparable to oil-based lubricants and superior to cationic surfactant analogue. Therefore, this NP is a potential efficient additive in water-based lubricating fluids. Graphical abstract: Highlights: A N-(3-(diethoxyphosphoryl)propyl)-N, N-dimethyloctadecan- 1-ammonium bromide (NP) was synthesized. The NP can significantly reduce the coefficient of friction to 0.076. The NP presents remarkable extreme-pressure and abrasion resistance behaviors. The NP significantly enhances the anti-friction capability of cationic surfactant by phosphonate functionality.